Family-Based Analyses Reveal Novel Genetic Overlap Between Cytokine Interleukin-8 and Risk for Suicide Attempt - Knowles, E. E. M. (Brain Behav Immun, 2019)
BACKGROUND: Suicide is major public health concern. It is imperative to find robust biomarkers so that at-risk individuals can be identified in a timely and reliable manner. Previous work suggests mechanistic links between increased cytokines and risk for suicide, but questions remain regarding the etiology of this association, as well as the roles of sex and BMI. METHODS: Analyses were conducted using a randomly-ascertained extended-pedigree sample of 1882 Mexican-American individuals (60% female, mean age=42.04, range=18-97). Genetic correlations were calculated using a variance components approach between the cytokines TNF-α, IL-6 and IL-8, and Lifetime Suicide Attempt and Current Suicidal Ideation. The potentially confounding effects of sex and BMI were considered. RESULTS: 159 individuals endorse a Lifetime Suicide Attempt. IL-8 and IL-6 shared significant genetic overlap with risk for suicide attempt (ρ(g)=0.49, p(FDR)=7.67x10(−3); ρ(g)=0.53, p(FDR)=0.01), but for IL-6 this was attenuated when BMI was included as a covariate (ρ(g)=0.37, se=0.23, p(FDR)=0.12). Suicide attempts were significantly more common in females (p(FDR)=0.01) and the genetic overlap between IL-8 and risk for suicide attempt was significant in females (ρ(g)=0.56, p(FDR)=0.01), but not in males (ρ(g)=0.44, p(FDR)=0.30). DISCUSSION: These results demonstrate that: IL-8 shares genetic influences with risk for suicide attempt; females drove this effect; and BMI should be considered when assessing the association between IL-6 and suicide. This finding represents a significant advancement in knowledge by demonstrating that cytokine alterations are not simply a secondary manifestation of suicidal behavior, but rather, the pathophysiology of suicide attempts is, at least partly, underpinned by the same biological mechanisms responsible for regulating inflammatory response.